Maksimalisasi Manajemen Kurikulum dalam Meningkatkan Kurikulum di MTs Al-Hikmah Lamongan - Novia Maharani Permatasari; Kusnul Khotimah (Departement of Mathematics Education, 2023)
The purpose of this study is to (1) know the curriculum management model in MTs Al-Hikamh Lamongan, (2) know the process of improving the quality of education in MTs Al-Hikmah Lamongan, (3) know what are the supporting factors and obstacles to the curriculum management process and quality improvement, (4) know the role of curriculum management in improving the quality of education in MTs Al-Hikamh Lamongan. This research is a type of field research with a descriptive qualitative approach. Data collection techniques are carried out by participatory observations, field observations, in-depth interviews and related documentation on the subject matter in the form of books, school documentation, internet media and various related sources. The results of this study are: (1) MTs Al-Hikamh Lamongan received a letter of appointment from the government as the implementer of the 2013 curriculum, so at this time MTs Al-Hikmah Lamongan still uses two curricula, namely KTSP and the 2013 curriculum. (2) The planning, development, implementation, and evaluation of the quirculum in MTs Al-Hikamh Lamongan shall be carried out comprehensively in accordance with the guidance of the 2013 curriculum. Although there are some obstacles that can still be handled. (3) MTs Al-Hikmah Lamongan strongly prioritizes improving the quality of schools. This is evidenced by the presence of the target of UN graduates who have reached 100% over the last 3 years. (4) The curriculum of MTs Al-Hikmah Lamongan holds a 95% contribution to the development of school quality. This is evidenced by implementing various innovations in changing learning models in schools.